2016
DOI: 10.1080/13696998.2016.1269015
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation for the US of nab-paclitaxel plus gemcitabine versus FOLFIRINOX versus gemcitabine in the treatment of metastatic pancreas cancer

Abstract: In the absence of a statistically significant difference in OS between NAB-P + GEM and FOLFIRINOX, this US analysis indicates that the greater economic benefit in terms of cost-savings and incremental cost-effectiveness and cost-utility ratios favors NAB-P + GEM over FOLFIRINOX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…31,32 However, there is a dearth of information regarding the economic outcome of maintenance treatments for MPC. Although 2 previous economic analyses have shown that a chemotherapy regimen containing nab-paclitaxel was cost-effective in the United States and United Kingdom, 20,33,34 these analyses included treatment-naïve patients with MPC. The target populations in those studies were different from ours in that the patients we studied had received at least 16 weeks of continuous first-line platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 However, there is a dearth of information regarding the economic outcome of maintenance treatments for MPC. Although 2 previous economic analyses have shown that a chemotherapy regimen containing nab-paclitaxel was cost-effective in the United States and United Kingdom, 20,33,34 these analyses included treatment-naïve patients with MPC. The target populations in those studies were different from ours in that the patients we studied had received at least 16 weeks of continuous first-line platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…8 The unit costs of managing fatigue and anemia were derived from the literature. [17][18][19][20] Each health state was assigned a health utility preference on a scale of 0 (death) to 1 (perfect health). Because the POLO trial 8 showed that EORTC Core Quality of Life Questionnaire (QLQ-C30) scores were similar between patients receiving maintenance olaparib and those receiving a placebo, we assumed that the health utility preference was only associated with the disease status.…”
Section: Cost and Utility Inputsmentioning
confidence: 99%
“…30 A Markov model also analyzed GnP, FOLFIRINOX, and gemcitabine as first-line treatment from an economic payer perspective in the US. 23 31 another Canadian analysis revealed FOLFIRINOX as cost effective, with an ICER below commonly quoted ICER thresholds for oncology products. Since then, the cost of oxaliplatin has considerably reduced, particularly as generic oxaliplatin is available almost worldwide.…”
Section: Benefit-risk Balance and Pharmacoeconomic Analysismentioning
confidence: 97%
“…30 A Markov model also analyzed GnP, FOLFIRINOX, and gemcitabine as first-line treatment from an economic payer perspective in the US. 23 Indirect comparisons suggest that GnP and FOLFIRINOX have statistically similar OS efficacy (HR, 0.79; 95% CI, 0.59-1.05). FOLFIRINOX prevailed in PFS efficacy (HR, 0.68; 95% CI, 0.51-0.91).…”
Section: Benefit-risk Balance and Pharmacoeconomic Analysismentioning
confidence: 99%
See 1 more Smart Citation